Blockchain, Fintech, and Islamic finance building the future in the new Islamic digital economy - Mohamed, Hazik (De Gruyter Press, 2019)
While creating new forms (Shari'ah-compliant standards) to operationalize Islamic values and ethics into the current conventional economic system and banking products is crucial to sustain the Islamic economy as it is today, we also need to develop new strategies to cope with the next economic evolution. The digital revolution in financial services is under way, and digital disruption has the potential to shrink the role and relevance of today's banks, while simultaneously creating better, faster, cheaper services that will be an essential part of everyday life. This forward-looking book discusses the crucial innovation, structural and institutional development for financial technologies (fintech) in Islamic finance. The authors explain concepts in fintech and blockchain technology and follow through with their applications, challenges and evolving nature. The book provides insights into technology which will enable and enhance actual prescribed Islamic behaviors in modern economic transactions. Case studies highlight how to cope with modern transactional behavior with the advent of global online/mobile markets, shorter attention spans, and impersonal trade exchange.